Conflict and Health - Roberts, Bayard
Conflict and Health brings together essential research on the intertwined relationship between health and conflict. Millions of people around the world are caught between the vicious spiral of violent conflict and poor health. The journal focuses on the intricate relationship between conflict and health, and how health interventions in war zones may contribute to peace.